Aquaponic Monitoring System using Internet of Things - Muhamad Yusof, Nurul Hasanah; Muhammad Audah, Lukman Hanif (Evolution in Electrical and Electronic Engineering, 2023)
Aquaponics is a progressive and eco-friendly agricultural technique that merges aquaculture, which involves fish farming, with hydroponics, a method of cultivating plants without soil. The efficiency and productivity of aquaponic systems rely heavily on maintaining optimal environmental conditions for both the fish and plants. To achieve this, continuous monitoring and control of various parameters such as water level, temperature of water and pH level are crucial. The objective of this work is to establish an aquaponic monitoring system designed to monitor and track the physical conditions of crops. This system will employ a range of sensors to actively detect the current physical conditions and then transmit this data to a NodeMCU ESP32 microcontroller. Then, the data such as pH, temperature, water level, and water pump will be processed by NodeMCU ESP32 and uploaded to the Blynk IoT Cloud. The pH sensor determines the acidity or alkalinity of the water in the fish tank. The ultrasonic sensor is used to measure the level of water. The DS18B20 waterproof temperature sensor is used to monitor the water temperature. The aquaponics monitoring system includes an alarm notification function to inform users about critical conditions from desired parameters promptly. When a parameter exceeds or falls below predefined thresholds, the system triggers an alarm notification in the Blynk application on the phone to designated users. In this work, the pH value is 6.97. The water temperature is about 29-30 ⁰C. Then, the water level is 12 litres. The enhancements introduced in aquaponic farming practices are anticipated to lead to a substantial increase in crop productivity and quality.